Patient access to psychiatric records: Experience in an in-patient unit - Kosky, N; Burns, T (1995)
Forty of 66 consecutive admissions to a psychiatric inpatient unit were encouraged to read their admission notes and discuss them with the junior doctor. The offer was withheld for two patients with organic impairment. Twenty-eight patients (including 12 on compulsory admissions) accepted the offer. The 12 who refused were characterised by overall lower educational attainment. Diagnosis raised only a few problems, prognosis and maintenance treatment being the locus of most discussions. There was no evidence of a deterioration in the quality of notes or therapeutic relationships as a consequence of access. Only in one case was the exercise judged 'harmful', but 'useful or essential' in 22. Possible benefits for both patients and doctor are explored.